Model of hypothecated tax on information goods - Oksana Melikhova (Charles University in Prague, Institute of Economic Studies (IES), 2012)
Information or knowledge, which can be incorporated in tangible objects at the same time in an unlimited number of copies at different locations anywhere in the world, constitutes Intellectual Property (IP) of an information producer. Intellectual property rights (IPR) legislation was created to optimize social welfare and to promote production of information by granting producers a temporary monopoly in return for a disclosure of their works. However, current IPR regimes are over-protective in terms of monopoly that is granted to a producer but they are under-protective against piracy and unauthorized use. Nowadays, the main effort is made to secure information in order to forbid unauthorized use, and thus this approach creates high barriers for information diffusion. The aim of the current work is to look for alternative solution of the IPR problem which can be defined as: how to profit from production of information without reduction its natural non-excludability and transferability. One of the possible solutions of IPR problem could be introduction of hypothecated tax on information goods. A theoretical model which describes exchange and production of the information goods was developed in support of the suggested solution. The case when production of the information goods is subsidized from the tax proceeds is also compared with the case when the information goods are sold on the market for unlimited flat rate. It was found that under assumption of homogeneous wealth and cost distributions the both cases result in the same consumption levels and the same condition on production costs.
Keywords: O34; O38; 330; Information good; Intellectual property rights; Hypothecated tax